Kajian Analisis dan Kontruksi Menara Pendingin - Review - Teguh Irawan (Jurnal Engine: Energi, Manufaktur, dan Material, 2022)
A cooling tower is a heat remover device that can be operated to transfer exile heat to the atmosphere. Generally, cooling towers are used to cool centrally flowed water and building cooling. The production process in the industrial world uses many large-scale machines. The process of these machines generates heat as a process of engine work, so it requires a cooling system for the working process. Cooling towers are very important for the industrial world. One of the functions of the cooling tower is as a heat exile around the environment, so it has a very important role in the industrial world. For Example, companies in the chemical sector, one of which is sulfa acid processing, H2O2 factories, and so on. There are different types of cooling towers operating, for example, heat exchangers, chillers, pumps, and compressors. Cooling tower performance depends on the mass flow rate of fluid, hot water temperature, and cold water temperature.